The efficacy of luliconazole and caspofungin on planktonic and biofilm of Candida albicans from different sources - Mahboubeh Shabanzadeh; Ali Rezaei-Matehkolaei; Ali Zarei Mahmoudabadi (Iranian Journal of Microbiology)
Background and Objectives: The ability of Candida albicans to produce biofilm is considered an important pathogenic factor. In addition, the low sensitivity of biofilms to antifungal drugs is a challenge for patients, clinicians, and laboratory workers. We aimed to investigate the effectiveness of luliconazole and caspofungin on the planktonic and biofilm types of C. albicans strains. Materials and Methods: Fifty C. albicans from vaginitis, candiduria, gastrointestinal candidiasis, and saliva were examined for antifungal susceptibility against caspofungin and luliconazole using the CLSI M27 guideline. Moreover, the susceptibility of biofilms was detected using 96 well microplates and the MTT method. Results: The capacity of the isolates to produce biofilm within 2, 6, and 24 h was different, however, all tested isolates produced biofilm after 24 h. Vaginal and esophagitis isolates had a high and low ability for biofilm production during 24-hour incubation. In our study, 90% of isolates were sensitive to caspofungin, while 7.5 and 2.5% of them were intermediate and resistant. The MIC range of all isolates against luliconazole was 0.01562-1 µg/mL. Conclusion: The MICs of biofilms were 15.6, and 171.3 higher than that of planktonic cells for caspofungin and luliconazole, respectively. Moreover, paradoxical and trailing effects occurred at 4 and 32 µg/mL of caspofungin and luliconazole, respectively.